Utilize Augmented Reality Technology to Improve Listening Skills in Foreign Languages - Rintaningrum, Ratna; Rahmawati, Rahmawati; Fionasari, Richa; Rahmawati, Istiqomah Nur; Safii, Muhammad (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Listening skills in a foreign language are an important component of an effective language learning process. Technological advances have opened up new opportunities to improve listening skills, one of which is through the use of Augmented Reality (AR) technology. This study aims to explain the potential use of AR in this context. The use of AR in foreign language learning provides an interactive and immersive experience for students. This technology allows users to combine the real world with digital elements, such as text or images, which can aid in the understanding and mastery of a foreign language. Various AR applications developed specifically for foreign language learning can create simulated situations where students can practice listening in real contexts. In addition, AR also allows personalization of learning. The AR system can be adapted to individual learners' ability levels, providing suitable exercises and challenges. This helps increase learning motivation and overall learning outcomes. This research also examines the challenges that may be faced in using AR, such as the accessibility of the technology and devices required, as well as the development of adequate content. However, as technology continues to develop, there are more and more opportunities to overcome these obstacles. In conclusion, the use of Augmented Reality technology can bring great benefits in improving listening skills in foreign languages. With the right approach and investment in the development of relevant technology and content, AR has the potential to become a valuable tool in foreign language education and can help students achieve higher levels of competency in foreign language listening. It is hoped that the results of this research can increase knowledge for pupils and students who utilize Augmented Reality Technology to Improve Listening Skills in Foreign Languages. The limitation of this research is that the researcher did not directly get involved in conducting this research, but instead distributed the questionnaire online.